Enhancing Client Satisfaction: Utilizing Feedback for Ongoing Improvement Strategies - Ronald A Gonzales; Mary Rose Montano; Aveto M Dasal Jr; Renante A Artificio; Anna Rhea C Opeña; Maria Mylin S Miranda; Meljhon G Mosca; Armando A Salenga Jr (Humanities, Society, and Community, 2025)
This study evaluated client satisfaction with the services provided by the City College of Calamba (CCC), with particular focus on the implementation of its Citizens' Charter and compliance with Republic Act No. 11032. Using a descriptive research design with 2,633 respondents, the study measured satisfaction across eight service quality dimensions, revealing an overall "Very Satisfactory" rating of 94.32%. The highest scores were in Reliability (95.46%) and Assurance (95.07%), while Costs (90.53%) and Learning Management System (LMS) support were identified as areas needing improvement. Statistical analysis using Goodman and Kruskal's Gamma Correlation demonstrated significant relationships between respondents' awareness of the Citizens' Charter and their satisfaction levels, highlighting the Charter's importance in service quality enhancement. Based on these findings, the study proposed a Continuous Improvement Plan (CIP) for FY 2026 focusing on digitization, staff training, and stakeholder engagement. However, the research had limitations, including reliance on self-reported data, which may introduce response bias, and its cross-sectional design, which limits causal interpretations. The study's focus on a single institution also affects the generalizability of results. For future research, longitudinal studies could assess the long-term impact of CIP implementation, while qualitative approaches, such as interviews, could provide deeper insights into satisfaction drivers. Comparative studies with other institutions would help identify best practices, particularly in addressing cost-related concerns and improving digital service delivery. These research directions would further strengthen CCC's governance framework and service excellence in line with national mandates and stakeholder needs.